Introduction. Beauty and Inequality: New Questions for a Fragmented Field - Kuipers, Giselinde; Sarpila, Outi; Brans, Luuc (Springer, 2026)
With this handbook, we aim to put the study of beauty and inequality on the map as a distinct research field. In contemporary societies beauty is not only a key cultural concern, but also a place where inequalities are increasingly played out, reproduced, and defined. This introduction to the Handbook of Beauty and Inequality provides an overview of the various ways researchers have tackled three key issues in the study of beauty and inequality: 1. What is beauty? 2. How does beauty shape inequality (or vice versa)? 3. How to study beauty and inequality empirically? On the basis of the answers to these questions, we distinguish seven research traditions. We show how disciplines as diverse as evolutionary psychology, sociology of stratification, economics, cultural and economic sociology, cultural studies, media and communication, social psychology, philosophy, ethnic and racial studies, disability studies and fat studies have tackled remarkably similar questions with vastly different methods and concepts.
Handbook of Beauty and Inequality